Sacral nerve stimulation: an effective treatment for chronic functional anal pain?. (18th September 2013) - Dudding, T. C.; Thomas, G. P.; Hollingshead, J. R. F.; George, A. T.; Stern, J.; Vaizey, C. J.
Abstract Aim Chronic idiopathic anal pain is a common condition of unknown aetiology. Patients may have co‐existing psychiatric disorders and existing treatments are often ineffective. A small number of published case reports suggest that sacral nerve stimulation (SNS) could treat this condition. This pilot study aimed to investigate the efficacy of SNS for the treatment of chronic anal pain. Method Ten patients with chronic idiopathic anal pain were recruited. All had failed to respond to conservative treatments. Clinical and psychological evaluation was performed in all patients prior to SNS. Temporary stimulation of the S3 foramina was performed for 3 weeks and outcome assessed by comparison of a pain score diary and visual analogue score obtained during stimulation and at baseline. Primary outcome was defined as a > 50% reduction in pain score. Results Of the 10 patients recruited, five were found to have clinical depression. Four patients withdrew from the study prior to testing and six underwent peripheral nerve evaluation (PNE). Three patients had > 50% reduction in pain score and progressed to permanent SNS. Of these, only one had good pain control at latest follow‐up of 5 years; the remaining two patients obtained no benefit and had their devices removed or deactivated. These two patients both had depression that was also not improved by SNS. Conclusion This study would suggest that SNS is not an effective treatment for chronic anal pain in the majority of patients. PNE is not an effective means of identifying which of these patients are likely to respond to permanent SNS.